Electrode for lithium secondary battery and method for producing same
By applying auxiliary coating on the current collector of the lithium-ion secondary battery electrode, the problem of N/P ratio instability caused by sliding is solved, and the electrical performance and safety of the battery are improved.
Patent Information
- Application Number
- JP2023543450
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-07
- Filing Date
- 2022-12-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-22
AI Technical Summary
When manufacturing the positive and negative electrodes of lithium-ion secondary batteries, the sliding phenomenon makes it difficult to maintain the N/P ratio constant, affecting the electrical performance and safety of the battery.
Apply an auxiliary coating on the current collector of the battery electrode, containing inorganic particles, phenolic compounds and binders, and the auxiliary coating covers the edges of the electrode mix layer by mold dies.
Through the use of auxiliary coating, the thickness difference between the edges of the electrode mixing layer is improved, the energy density of the battery and the adhesion of the separation membrane are improved, and lithium ions are prevented from depositing at the end of the electrode, which improves the safety of the battery.
Smart Images

Figure 0007658670000005 
Figure 0007658670000006 
Figure 0007658670000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a lithium secondary battery and a method for producing the same.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0002814 dated January 7, 2022, and all contents disclosed in the documents of said Korean patent application are incorporated herein by reference. [Background technology]
[0003] In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.
[0004] Such secondary batteries are power generating elements capable of being charged and discharged and have a laminated structure of a positive electrode / separator / negative electrode. In general, the positive electrode contains a lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based negative electrode active material such as graphite. During charging, lithium ions released from the positive electrode are absorbed into the carbon-based negative electrode active material of the negative electrode, and during discharging, the lithium ions contained in the carbon-based negative electrode active material are absorbed into the lithium metal oxide of the positive electrode, thereby allowing repeated charging and discharging.
[0005] One of the factors that influence the performance of a secondary battery is the capacity ratio of the active materials contained in the positive and negative electrodes. The capacity ratio of each electrode active material can be expressed as the N / P ratio, which is the total capacity of the negative electrode calculated taking into account the capacity per area and / or weight of the negative electrode, divided by the total capacity of the positive electrode calculated taking into account the capacity per area and / or weight of the positive electrode, and is generally adjusted to have a value of 1 or more since it has a significant effect on the safety and capacity of the battery.
[0006] However, since a sliding phenomenon is induced at the ends of the electrode mixture layer containing the active material during the manufacture of the positive and negative electrodes, it is difficult to maintain a constant N / P ratio of the positive and negative electrodes. This can lead to problems such as a decrease in the electrical performance of the battery and a decrease in safety due to lithium precipitation at the ends of the electrodes, particularly the negative electrode end. Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to provide a technology that can prevent the reversal of the N / P ratio between the positive electrode and the negative electrode of a lithium secondary battery, thereby preventing a deterioration in the electrical performance of the secondary battery, while further improving the safety of the battery. [Means for solving the problem]
[0008] In order to solve the above-mentioned problems, in one embodiment, the present invention provides an electrode for a lithium secondary battery, comprising: an electrode current collector; an electrode mixture layer provided on the electrode current collector and containing an electrode active material; and an auxiliary coating layer provided on the electrode current collector and located at an end of the electrode mixture layer, wherein the electrode mixture layer has a difference (|ab|) between a length (a) of a surface in contact with the electrode current collector and a length (b) of a surface not in contact with the electrode current collector of 8 mm or less.
[0009] In this case, the auxiliary coating layer may include inorganic particles, a phenolic compound, and a binder.
[0010] The inorganic particles may include one or more of the aluminum minerals boehmite, gibbsite, diaspore, alunite, and nepheline.
[0011] In addition, the phenolic compound may include one or more of tannic acid, baicalein, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, piceatannol, pyrogallic acid, ellagic acid, amylose, amylopectin, and xanthan gum.
[0012] The auxiliary coating layer may contain inorganic particles in an amount of 50% by weight or more based on the total weight of the layer.
[0013] In addition, the auxiliary coating layer has a structure surrounding the end surface of the electrode mixture layer, can form one layer with the electrode mixture layer, and can have a thickness that is 70% to 100% of the average thickness of the electrode mixture layer.
[0014] The end of the electrode mixture layer may have an inclination angle of 50° or more.
[0015] Furthermore, in one embodiment, the present invention provides a method for manufacturing an electrode for a lithium secondary battery, the method comprising the step of simultaneously coating an electrode slurry containing an electrode active material and an auxiliary coating composition on an electrode collector to manufacture an electrode in which an auxiliary coating layer is disposed on an end of an electrode mixture layer containing an electrode active material, wherein the electrode mixture layer has a difference (|ab|) between a length (a) of a surface in contact with the electrode collector and a length (b) of a surface not in contact with the electrode collector of 8 mm or less.
[0016] Here, the auxiliary coating composition may include inorganic particles, a phenolic compound, and a binder.
[0017] The inorganic particles may be contained in an amount of 50% by weight or more based on the total weight of the auxiliary coating composition.
[0018] In addition, the phenolic compound may include one or more of tannic acid, baicalein, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, piceatannol, pyrogallic acid, ellagic acid, amylose, amylopectin, and xanthan gum.
[0019] The phenol compound may be contained in an amount of 0.1 to 5% by weight based on the total weight.
[0020] In addition, the electrode slurry and the coating of the auxiliary coating composition are simultaneously discharged by a slot die, and the slot die includes an upper die having a chamber for accommodating the electrode slurry, a lower die facing the upper die, and a plate-shaped shim member located between the upper and lower dies, having a hollow in its body communicating with the chamber, and provided with an outlet for discharging the electrode slurry from the hollow, and may include supply grooves at both ends of the outlet of the shim member for supplying the auxiliary coating composition.
[0021] The shim member may include a partition wall that divides the hollow space so that the electrode slurry is separately discharged into the body, and the partition wall may have a supply groove that supplies an auxiliary coating composition to an edge of each of the electrode slurries that are separately discharged.
[0022] In addition, the supply groove may include a through-portion penetrating the shim member in a thickness direction, and the through-portion may be formed a predetermined length inward from a discharge lip through which the auxiliary coating composition is discharged.
[0023] The discharge port and the supply groove of the shim member may be structured to contact each other on the inside with respect to one side surface of the upper die and the lower die on which the discharge port and the discharge lip are provided. Effect of the Invention
[0024] The electrode for a lithium secondary battery according to the present invention has an auxiliary coating layer including inorganic particles, a phenol compound, and a binder at an end of an electrode mixture layer including an electrode active material, the auxiliary coating layer having a predetermined thickness so as to surround or cover the surface. This improves the thickness difference at the end of the electrode mixture layer, thereby improving the energy density of the battery and the adhesive strength of the separator at the electrode end, and preventing lithium from being deposited at the electrode, particularly at the negative electrode end, resulting in excellent safety. [Brief description of the drawings]
[0025] [Figure 1] 1A and 1B are cross-sectional views illustrating one side end of an electrode mixture layer provided in an electrode for a lithium secondary battery, in which (a) shows the cross-sectional structure of a conventional electrode, and (b) shows the cross-sectional structure of an electrode according to the present invention. [Diagram 2] FIG. 1 is a perspective view showing a schematic structure of a slot die according to the present invention. [Diagram 3] FIG. 4 is a plan view showing an example of a shim member according to the present invention. [Figure 4] 11 is a perspective view showing the structure of a supply groove provided in the main body and / or the partition wall of the shim member. FIG. [Diagram 5] 13 is a plan view showing a discharge port and an inlet of a supply groove provided in a shim member. FIG. [Figure 6] 4A to 4C are cross-sectional views illustrating the end structures of the electrode mixture layers of the positive and negative electrodes with and without the respective auxiliary coating layers. [Figure 7] 4A to 4C are cross-sectional views illustrating the end structures of the electrode mixture layers of the positive and negative electrodes with and without the respective auxiliary coating layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Because the present invention can be modified in various ways and can have various embodiments, specific embodiments will be described in detail in the detailed description.
[0027] However, this is not intended to limit the invention to any particular embodiment, but is to be understood as including all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.
[0028] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, but are understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0029] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.
[0030] In addition, in the present invention, "containing as a main component" can mean 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 97.5% by weight or more based on the total weight of a composition such as a slurry or a specific component, and in some cases can mean 100% by weight when constituting the entire composition or specific component.
[0031] In the present invention, the "sliding angle" of the end of the electrode mixture layer refers to the angle at which the electrode mixture layer provided on the electrode current collector slides from the inside to the outside as shown in FIG. 1, and has a certain angle with respect to the electrode current collector at the time of observing the cross section of the electrode mixture layer. At this time, the angle induced from the end of the electrode mixture layer by the sliding of the electrode mixture layer can mean the sliding angle of the electrode mixture layer, and can also be the "end inclination angle" of the electrode mixture layer.
[0032] The present invention will now be described in more detail.
[0033] <Electrodes for lithium secondary batteries> In one embodiment, the present invention comprises: Electrode current collector, an electrode mixture layer provided on the electrode current collector and containing an electrode active material; and An auxiliary coating layer is provided on the electrode current collector and located at an end of the electrode mixture layer, The electrode mixture layer provides an electrode for a lithium secondary battery, in which the difference (|ab|) between the length (a) of the surface in contact with the electrode current collector and the length (b) of the surface not in contact with the electrode current collector is 8 mm or less.
[0034] The electrode for a lithium secondary battery according to the present invention includes an electrode mixture layer containing an electrode active material on an electrode current collector, and an auxiliary coating layer is provided on the edge, i.e., the end, of the electrode mixture layer, and the electrode mixture layer and the auxiliary coating layer form a single layer. The electrode of the present invention can improve the sliding phenomenon at the end of the electrode mixture layer as shown in FIG. 1(b) by providing the auxiliary coating layer on the end of the electrode mixture layer. As a result, the electrode can suppress the occurrence of a difference in thickness at the end of the electrode mixture layer, and therefore has an excellent effect of improving the energy density of the battery. In addition, the electrode has an excellent effect of improving the durability and / or safety of the battery, since the adhesive strength at the end to the separator is increased.
[0035] In this case, the auxiliary coating layer may be prepared by simultaneously applying an auxiliary coating composition for forming the auxiliary coating layer to an edge of the applied electrode slurry when the electrode slurry for forming the electrode mixture layer is applied to the electrode current collector.
[0036] In addition, the auxiliary coating layer has a shape that surrounds or covers the end surface of the electrode mixture layer, and thus has a structure that forms one layer together with the electrode mixture layer. Specifically, the auxiliary coating composition that is applied simultaneously with the electrode slurry contacts the end surface of the electrode slurry to form a shape that surrounds or covers the end of the electrode slurry, and the electrode mixture layer and the auxiliary coating layer are formed by drying the electrode slurry and the auxiliary coating composition in such a shape. Here, the end surface may mean an area exposed on the side of the electrode mixture layer. In addition, the height of the auxiliary coating layer derived from the auxiliary coating composition may have a ratio of 70% to 100% based on the average height of the electrode slurry (or electrode mixture layer), and specifically may have a ratio of 75% to 100%, 80% to 100%, 90% to 100%, 70% to 95%, 70% to 90%, 70% to 85%, or 80% to 90%.
[0037] By controlling the shape and / or height of the auxiliary coating layer as described above, the present invention can realize a dam function that prevents the edge region of the electrode slurry applied during the formation of the electrode mixture layer from being pushed outward due to a sliding phenomenon.
[0038] In addition, the auxiliary coating layer may include a component that can improve the sliding phenomenon of the electrode mixture layer end, and the component may exhibit insulating properties. Specifically, the auxiliary coating layer may include inorganic particles, a phenolic compound, and a binder.
[0039] Here, the inorganic particles may function as a main component of the auxiliary coating layer to suppress the sliding phenomenon at the end of the electrode mixture layer. Such inorganic particles may include one or more aluminum minerals selected from the group consisting of boehmite, gibbsite, diaspore, alumite, and nepheline.
[0040] In addition, the phenol compound may increase the dispersibility of inorganic particles contained in the auxiliary coating layer, while allowing the binder to be distributed in a large amount on the surface of the auxiliary coating layer, thereby increasing the adhesive strength of the end of the electrode composite layer to the separator. Such phenol compounds may include at least one of tannic acid, baicalein, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, piceatannol, pyrogallic acid, ellagic acid, amylose, amylopectin, and xanthan gum.
[0041] In addition, the binder may be any binder commonly used in the art for lithium secondary battery electrodes without any particular limitations. Specifically, the binder may include at least one of polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer, polychlorotrifluoroethylene, vinylidene fluoride-pentafluoropropylene copolymer, propylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene copolymer, ethylene-acrylic acid copolymer, and carboxymethyl cellulose (CMC).
[0042] In addition, the auxiliary coating layer may be controlled so that the content of inorganic particles and phenolic compounds meets a certain range. Specifically, the inorganic particles may be contained in the auxiliary coating layer at 50% by weight or more, 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 97.5% by weight or more based on the weight of the entire auxiliary coating layer, and more specifically, the inorganic particles may be contained in the auxiliary coating layer at 50-90% by weight, 50-80% by weight, 55-85% by weight, 50-65% by weight, 60-80% by weight, 65-85% by weight, or 70-85% by weight based on the weight of the entire auxiliary coating layer.
[0043] By controlling the content of inorganic particles within the above-mentioned range, the present invention can prevent the effect of suppressing the sliding phenomenon of the electrode mixture layer from becoming insignificant due to a low content, and can prevent the detachment of inorganic particles from the surface of the auxiliary coating layer due to a high content.
[0044] The phenol compound may be contained in an amount of 0.01 to 5% by weight, specifically 0.1 to 3% by weight, 1 to 3% by weight, or 1.5 to 2.5% by weight, based on the total weight of the auxiliary coating layer.
[0045] By controlling the content of the phenol compound within the above range, the present invention can prevent the inorganic particles from agglomerating in the auxiliary coating layer due to a low content, or from precipitating due to phase instability of the coating composition during the preparation of the auxiliary coating layer, and can prevent the adhesive strength of the auxiliary coating layer to the electrode current collector from decreasing due to a high content.
[0046] As an example, the auxiliary coating layer may include 72-78 wt % inorganic particles, 1.8-2.2 wt % phenolic compound, and 19.8-26.2 wt % binder.
[0047] In the electrode for a lithium secondary battery according to the present invention, the sliding phenomenon at the end of the electrode mixture layer can be improved by providing the auxiliary coating layer on the edge, i.e., the end, of the electrode mixture layer as described above.
[0048] For example, the electrode for a lithium secondary battery according to the present invention may have a difference in length between both sides of the electrode mixture layer, i.e., the difference (|ab|) between the length (a) of the surface in contact with the electrode current collector and the length (b) of the surface not in contact with the electrode current collector, of 8 mm or less. Specifically, the electrode may have a difference in length between both sides of the electrode mixture layer (|ab|) of 7 mm or less, 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, or 0.5 mm or less, and in some cases may have a difference in length of 0.5 mm or less.
[0049] 1 is a cross-sectional view showing one end of an electrode mixture layer, and when no auxiliary coating layer is provided, the sliding phenomenon occurs significantly at the end of the electrode mixture layer as shown in (a), and as a result, the difference (|ab| or 2c) between the length (a) of the surface in contact with the electrode current collector and the length (b) of the surface not in contact with the electrode current collector exceeds 8 mm. However, by providing an auxiliary coating layer in the electrode according to the present invention, the sliding phenomenon occurring at the end of the electrode mixture layer as shown in (b) is suppressed, and the difference (|ab| or 2c) between the length (a) of the surface in contact with the electrode current collector and the length (b) of the surface not in contact with the electrode current collector is reduced to 8 mm or less.
[0050] For example, in the lithium secondary battery electrode, the difference (|ab|) between the length (a) of the surface in contact with the electrode current collector and the length (b) of the surface not in contact with the electrode current collector may be 2.5 to 3.5 mm in the case of a negative electrode, and 0.05 to 0.5 mm in the case of a positive electrode.
[0051] In addition, the electrode for a lithium secondary battery of the present invention may have a sliding angle, i.e., an inclination angle, of an end portion of an electrode mixture layer of 50° or more. Specifically, the inclination angle of the end portion of the electrode mixture layer may be 60° or more, 70° or more, 80° or more, 90° or more, or 100° or more, and more specifically, 50° to 120°, 60° to 110°, 70° to 100°, 75° to 95°, or 80° to 95°.
[0052] By controlling the difference in length between both sides of the electrode mixture layer and / or the inclination angle of the ends within the above range, the present invention can control the N / P ratio, which indicates the ratio of the capacity of the positive electrode to the capacity of the negative electrode, to a value of 1 or more, thereby improving the safety and capacity of the battery.
[0053] Meanwhile, the lithium secondary battery electrode of the present invention can be applied to both the positive electrode and the negative electrode used in the lithium secondary battery.
[0054] When the lithium secondary battery electrode is a positive electrode, the electrode current collector may be one having high conductivity without inducing chemical changes in the battery, such as stainless steel, aluminum, nickel, titanium, calcined carbon, etc., and in the case of aluminum or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc.
[0055] In addition, the positive electrode current collector can have fine irregularities on its surface to enhance the adhesive strength of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. In addition, the average thickness of the current collector can be suitably 3 to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.
[0056] In addition, the electrode mixture layer provided on the electrode current collector may contain a positive electrode active material, and may further selectively contain a conductive material, a binder, an additive, and the like, as necessary.
[0057] In this case, the positive electrode active material is a positive electrode active material capable of reversible intercalation and deintercalation, and may include at least one of a lithium metal composite oxide represented by the following Chemical Formula 1 and a lithium iron phosphate compound represented by the following Chemical Formula 2.
[0058] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O u
[0059] [Chemical formula 2] Life 1-p M 2 p PO q
[0060] In the above chemical formulas 1 and 2, M 1is one or more doping elements selected from the group consisting of W, Cu, Fe, V, Cr, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and x, y, z, w, v and u are 1.0≦x≦1.30, 0.6≦y<0.95, 0.01 <z≦0.5、0.01<w≦0.5、0≦v≦0.2、1.5≦u≦4.5であり、M 2 is one or more doping elements selected from the group consisting of Ni, Co, Mn and V, and p and q are 0.05≦p≦0.2 and 2≦q≦6, respectively.
[0061] In one example, the positive electrode active material may include a lithium metal composite oxide including nickel (Ni), cobalt (Co) and manganese (Mn), and the lithium metal composite oxide may optionally include other transition metals (M 1 In a specific example, the positive electrode active material may be doped with Li(Ni 0.6 Co 0.2 Mn 0.2 )O 2 , Li(Ni 0.7 Co 0.15 Mn 0.15 )O 2 , Li(Ni 0.8 Co 0.1 Mn 0.1 )O 2 , Li(Ni 0.9 Co 0.05 Mn 0.05 )O 2 , Li(Ni 0.6 Co 0.2 Mn 0.1 Zr 0.1 )O 2 , Li(Ni 0.6 Co 0.2 Mn 0.15 Zr 0.05 )O 2 and Li(Ni 0.7 Co 0.1 Mn 0.1 Zr 0.1 )O 2 The composition may include one or more selected from the group consisting of:
[0062] In another example, the positive electrode active material may include a lithium phosphate compound containing iron, and the lithium phosphate compound may optionally contain other transition metals (M 2 For example, the lithium iron phosphate compound may have a doped form of LiFePO 4 , Life 0.8 Mn 0.2 PO 4 , and LiFe 0.5 Mn 0.5 PO 4 It may contain one or more of the following.
[0063] The content of the positive electrode active material may be 85 to 95 parts by weight, specifically 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight, per 100 parts by weight of the positive electrode mixture layer.
[0064] In addition, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.
[0065] As an example, the conductive material may be carbon black or denka black, which may be used alone or in combination.
[0066] The conductive material may be contained in an amount of 0.1 to 5 parts by weight, specifically 0.1 to 4 parts by weight; 2 to 4 parts by weight; 1.5 to 5 parts by weight; 1 to 3 parts by weight; 0.1 to 2 parts by weight; or 0.1 to 1 part by weight, relative to 100 parts by weight of the positive electrode mixture layer.
[0067] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one resin selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.
[0068] The electrode mixture layer may contain the binder in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, relative to 100 parts by weight of the total; or the conductive material in an amount of 1 to 5 parts by weight.
[0069] Furthermore, the average thickness of the electrode mixture layer is not particularly limited, but may specifically be 50 μm to 300 μm, and more specifically may be 100 μm to 200 μm; 80 μm to 150 μm; 120 μm to 170 μm; 150 μm to 300 μm; 200 μm to 300 μm; or 150 μm to 190 μm.
[0070] When the lithium secondary battery electrode is a negative electrode, the electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, nickel, titanium, calcined carbon, etc. may be used. In the case of copper or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. may also be used.
[0071] In addition, the negative electrode current collector may have fine irregularities on its surface to strengthen the bonding force with the negative electrode active material, similar to the positive electrode current collector, and may be in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven fabric, etc. The average thickness of the negative electrode current collector may be preferably 3 to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.
[0072] The negative electrode active material may include, for example, one or more of a carbon material and a silicon material. The carbon material means a carbon material mainly composed of carbon atoms, and examples of such carbon materials include graphite having a completely layered crystal structure such as natural graphite, soft carbon having a low-crystalline layered crystal structure (graphene structure; a structure in which planes of a hexagonal honeycomb pattern of carbon are arranged in layers), and hard carbon in which these structures are mixed with non-crystalline parts, artificial graphite, expanded graphite, carbon fiber, non-graphitizable carbon, carbon black, acetylene black, ketjen black, carbon nanotubes, fullerene, activated carbon, graphene, etc., and preferably includes one selected from the group consisting of natural graphite, artificial graphite, graphene, and carbon nanotubes. More preferably, the carbon material includes natural graphite and / or artificial graphite, and may include any one of graphene and carbon nanotubes together with the natural graphite and / or artificial graphite. In this case, the carbon substance may contain 0.1 to 10 parts by weight of graphene and / or carbon nanotubes relative to 100 parts by weight of the total carbon substance, and more specifically, may contain 0.1 to 5 parts by weight; or 0.1 to 2 parts by weight of graphene and / or carbon nanotubes relative to 100 parts by weight of the total carbon substance.
[0073] The silicon material is a particle containing silicon (Si) as a metal component as a main component, and is composed of silicon (Si) particles and silicon oxide (SiO x , 1≦x≦2) particles. As an example, the silicon material may include one or more of silicon (Si) particles, silicon monoxide (SiO) particles, silicon dioxide (SiO 2 ) particles, or a mixture of these particles.
[0074] In addition, when the silicon material is used as a negative electrode active material together with a carbon material, the silicon material may be included in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the negative electrode mixture layer, specifically, 5 to 20 parts by weight, 3 to 10 parts by weight, 8 to 15 parts by weight, 13 to 18 parts by weight, or 2 to 7 parts by weight relative to 100 parts by weight of the negative electrode mixture layer.
[0075] By adjusting the content of the silicon material contained in the negative active material within the above range, the present invention can improve the charge capacity per unit mass while reducing the lithium consumption and irreversible capacity loss during the initial charge and discharge of the battery.
[0076] As an example, the negative electrode active material may be a mixture of 95±2 parts by weight of graphite, silicon monoxide (SiO) particles, and silicon dioxide (SiO 2 The present invention may include 5±2 parts by weight of a mixture in which the carbon material and silicon material contained in the negative electrode active material are uniformly mixed. By adjusting the contents of the carbon material and silicon material contained in the negative electrode active material within the above ranges, the present invention can reduce the lithium consumption and irreversible capacity loss during the initial charge and discharge of the battery, and improve the charge capacity per unit mass.
[0077] The negative electrode mixture layer may have an average thickness of 100 μm to 200 μm, specifically, 100 μm to 180 μm, 100 μm to 150 μm, 120 μm to 200 μm, 140 μm to 200 μm, or 140 μm to 160 μm.
[0078] The lithium secondary battery electrode according to the present invention has the above-mentioned configuration, and therefore the thickness difference at the ends of the electrode mixture layer is improved, thereby improving the energy density of the battery, and the adhesive strength of the separator at the electrode ends is improved, thereby preventing lithium from being deposited at the electrode, particularly at the negative electrode end. In other words, it has the advantage of being excellent in safety.
[0079] <Method of manufacturing electrodes for lithium secondary batteries> In one embodiment, the present invention provides a method for manufacturing an electrode for a lithium secondary battery, the method comprising the steps of simultaneously coating an electrode slurry containing an electrode active material and an auxiliary coating composition on an electrode collector to manufacture an electrode in which an auxiliary coating layer is disposed on an end of an electrode mixture layer containing an electrode active material, wherein the electrode mixture layer has a difference (|ab|) between a length (a) of a surface in contact with the electrode collector and a length (b) of a surface not in contact with the electrode collector of 8 mm or less.
[0080] The method for manufacturing an electrode for a lithium secondary battery according to the present invention is a method for manufacturing the above-mentioned electrode for a lithium secondary battery, and includes a step of simultaneously coating an electrode slurry containing an electrode active material and an auxiliary coating composition on an electrode current collector to manufacture an electrode having a structure in which an electrode mixture layer containing an electrode active material and an auxiliary coating layer are disposed on an end of the electrode mixture layer.
[0081] The present invention can improve the sliding phenomenon at the end of the electrode mixture layer by simultaneously coating an electrode slurry for forming the electrode mixture layer and an auxiliary coating composition for forming an auxiliary coating layer provided at the end of the electrode mixture layer when forming the electrode mixture layer. As a result, the present invention can suppress the occurrence of thickness differences at the end of the electrode mixture layer, thereby improving the energy density of the battery. In addition, the manufactured electrode has an increased adhesive strength at the end to the separator, thereby improving the durability and / or safety of the battery.
[0082] As an example, the electrode for a lithium secondary battery manufactured by the above manufacturing method may have a difference in length between both sides of the electrode mixture layer, i.e., the difference (|ab|) between the length (a) of the surface in contact with the electrode current collector and the length (b) of the surface not in contact with the electrode current collector, of 8 mm or less. Specifically, the electrode may have a difference in length between both sides of the electrode mixture layer (|ab|) of 7 mm or less, 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, or 0.5 mm or less, and in some cases may be 0.5 mm or less.
[0083] In the method for producing an electrode according to the present invention, the auxiliary coating composition may contain inorganic particles, a phenolic compound, and a binder.
[0084] Specifically, the inorganic particles, as the main component of the auxiliary coating layer, can suppress the sliding phenomenon at the end of the electrode mixture layer. Such inorganic particles can include one or more aluminum minerals selected from the group consisting of boehmite, gibbsite, diaspore, alumite, and nepheline.
[0085] In addition, the phenol compound may increase the dispersibility of inorganic particles contained in the auxiliary coating layer, while allowing the binder to be distributed in a large amount on the surface of the auxiliary coating layer, thereby increasing the adhesive strength of the end of the electrode composite layer to the separator. Such phenol compounds may include at least one of tannic acid, baicalein, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, piceatannol, pyrogallic acid, ellagic acid, amylose, amylopectin, and xanthan gum.
[0086] In addition, the binder may be any binder commonly used in the art for lithium secondary battery electrodes without any particular limitations. Specifically, the binder may include at least one of polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer, polychlorotrifluoroethylene, vinylidene fluoride-pentafluoropropylene copolymer, propylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene copolymer, ethylene-acrylic acid copolymer, and carboxymethyl cellulose (CMC).
[0087] In addition, the auxiliary coating composition may be controlled so that the content of inorganic particles and phenolic compounds meets a certain range. Specifically, the inorganic particles may be included in an amount of 50 wt% or more, 55 wt% or more, 60 wt% or more, 65 wt% or more, 70 wt% or more, 80 wt% or more, 90 wt% or more, 95 wt% or more, or 97.5 wt% or more based on the total weight of the auxiliary coating composition, and more specifically, the inorganic particles may be included in an amount of 50-90 wt%, 50-80 wt%, 55-85 wt%, 50-65 wt%, 60-80 wt%, 65-85 wt%, or 70-85 wt% based on the total weight of the auxiliary coating layer.
[0088] By controlling the content of inorganic particles within the above-mentioned range, the present invention can prevent the effect of suppressing the sliding phenomenon of the electrode mixture layer from becoming insignificant due to a low content, and can prevent the detachment of inorganic particles from the surface of the auxiliary coating layer due to a high content.
[0089] The phenol compound may be included in an amount of 0.01 to 5 wt %, more specifically, 0.1 to 3 wt %, 1 to 3 wt %, or 1.5 to 2.5 wt %, based on the total weight of the auxiliary coating composition.
[0090] By controlling the content of the phenol compound within the above range, the present invention can prevent the inorganic particles from agglomerating in the auxiliary coating composition due to a low content, or from precipitating due to phase instability of the coating composition during preparation of the auxiliary coating composition, and can prevent the adhesive strength of the auxiliary coating layer to the electrode current collector from decreasing due to a high content.
[0091] As an example, the auxiliary coating composition may include 72-78 wt. % inorganic particles, 1.8-2.2 wt. % phenolic compound, and 19.8-26.2 wt. % binder.
[0092] Furthermore, the coating of the electrode slurry and the auxiliary coating composition can be performed by a simultaneous coating method commonly used in the art, specifically, by a slot die as shown in FIG.
[0093] The slot die 100 includes an upper die 110 having a chamber for accommodating an electrode slurry, a lower die 120 facing the upper die, and a plate-shaped shim member 130 located between the upper and lower dies, having a hollow in its body communicating with chamber C, and provided with an outlet for discharging the electrode slurry from the hollow. The shim member 130 may include supply grooves 135 for supplying an auxiliary coating composition at both ends of the outlet 134.
[0094] Here, the upper die 110 and the lower die 120 are coupled to each other to form a die part, and the upper die 110 and the lower die 120 may be coupled to each other directly or indirectly via an intermediate medium. The upper die 110 and the lower die 120 are coupled to each other at their edge regions to form an internal space, i.e., a chamber. At this time, the internal space is a space where the electrode slurry is accommodated and retained before being discharged to the outside through the discharge port.
[0095] In addition, the shim member 130 is interposed between the upper die 110 and the lower die 120 when the upper die 110 and the lower die 120 are joined together, and has a hollow 132 penetrating the center thereof, so that the shim member 130 communicates with the chamber formed by the die parts. As a result, both the chamber and the hollow form a space in which the electrode slurry is stored.
[0096] 3 is an example showing a planar structure of a shim member 130 according to the present invention, and the shim member 130 has a plate-shaped body 131, and the body 131 has a hollow 132 communicating with a chamber of an upper die of a die. The hollow 132 includes an outlet 134 for discharging the electrode slurry supplied from the chamber to one side of the body 131, and supply grooves 135 for supplying an auxiliary coating composition are provided at both ends of the outlet 134. That is, the one side of the body 131 on which the outlet 134 is formed may further include supply grooves 135 for supplying an auxiliary coating composition on both sides of the outlet 134.
[0097] Here, as shown in Fig. 3(b) and (c), the shim member 130 may include one or more partitions 133 dividing the hollow 132 so that the electrode slurry is separately discharged into the main body 131. The partitions 133 may have supply grooves 135 for supplying an auxiliary coating composition to the edge of each electrode slurry to be separately discharged. The shim member 130 is capable of multi-thermal coating by including the partitions 133 dividing the hollow, and the supply grooves 135 provided in the partitions 133 may include two discharge lips 136 at the lower end of each partition 133 so that the auxiliary coating composition can be supplied adjacent to both edges of the discharged electrode slurry.
[0098] In addition, FIG. 4 is a perspective view showing the structure of the supply groove 235 provided in the main body 231 and / or the partition 233 of the shim member, and the supply groove 235 includes a through portion 237 provided in the main body 231 and / or the partition 233 of the shim member 230 and penetrating in the thickness direction of the shim member 230 so as to supply the auxiliary coating composition to both sides of the discharge port, and the through portion 237 may have a structure formed a predetermined length from the entrance of the supply groove 235 from which the auxiliary coating composition is discharged, i.e., the discharge lip 236, inside the main body.
[0099] Conventionally, the shim member used in the slot die applied in the industry includes a discharge port and / or a supply groove, and the discharge port and the supply groove have a structure that is partially blocked so as to have a step of a certain length from the discharge lip of the supply groove inward like a groove in order to arrange the height of the flow path where the auxiliary coating composition is finally supplied higher than the height of the flow path of the electrode slurry. In this case, the amount of the composition remaining inside the slot die increases due to the step of the discharge lip from which the auxiliary coating composition is discharged, so that the electrode slurry can be more stably and uniformly coated when the electrode mixture layer is formed. However, as described above, when the step is induced at the entrance of the supply groove to make the height of the flow path higher than the discharge port from which the electrode slurry is discharged, the auxiliary coating composition is coated biased toward the downstream side, so that the auxiliary coating layer cannot sufficiently prevent the sliding phenomenon of the electrode mixture layer.
[0100] However, the shim member 230 used in the present invention has a supply groove 235 having a through-portion 237 penetrating in the thickness direction of the shim member a predetermined length inward from the inlet through which the auxiliary coating composition is discharged, thereby increasing the amount of the auxiliary coating composition that remains inside the slot die while preventing the auxiliary coating composition from being biased toward the downstream side.
[0101] Furthermore, FIG. 5 is a plan view showing the structure of the discharge port 334 and the inlet (i.e., discharge lip 336) of the supply groove 335 provided in the shim member 330, and the shim member 330 can be located between the upper die and the lower die, and can be located inside the upper die and the lower die where the surfaces on which the discharge port 334 for discharging the electrode slurry and the discharge lip 336 for discharging the auxiliary coating composition are formed overlap.
[0102] Specifically, when the shim member is interposed between the upper die and the lower die, the discharge lips 336 for discharging the auxiliary coating composition may be provided at both inner ends of the discharge port 334 for discharging the electrode slurry. Thus, the discharge port 334 and the discharge lip 336 provided in the shim member may be structured to contact each other at a point 338 spaced inward by a predetermined length based on one side of the upper die and the lower die where they are located.
[0103] At this time, the discharge port 334 and the discharge lip 336 may contact each other at a point spaced about 10 μm to 1,000 μm inward from one side of the overlapped upper die and lower die (e.g., a surface perpendicular to the joining surface between the upper die and the lower die), more specifically, at a point spaced about 50 μm to 750 μm; 50 μm to 500 μm; 200 μm to 400 μm; or 80 μm to 200 μm inward.
[0104] In the present invention, the discharge port 334 and the discharge lip 336 of the shim member 330 are located inside the upper die and the lower die, so that the electrode slurry supplied from the discharge port and the auxiliary coating composition supplied from the supply groove can be discharged simultaneously in a state of contact inside the die before reaching the electrode current collector. As a result, the auxiliary coating composition discharged simultaneously can be embodied in a form that surrounds or covers the surface of the end at a height ratio of 70% to 100% compared to the average height of the applied electrode slurry, so that the sliding phenomenon of the electrode slurry can be more effectively prevented. However, when the discharge port 334 and the discharge lip 336 are not in contact with each other inside the upper die and the lower die as in the present invention, and the discharge lip 336 is discharged simultaneously from both outer ends of the body where the discharge port 334 is formed, the auxiliary coating composition is not formed at the end of the electrode slurry with a sufficient thickness compared to the average height of the applied electrode slurry, so there is a limitation that the function of the auxiliary coating composition as a dam is not fully exhibited.
[0105] The method for manufacturing a lithium secondary battery according to the present invention has the above-mentioned configuration, and thus can improve the sliding phenomenon of the electrode slurry constituting the electrode mixture layer, thereby improving the thickness difference at the ends of the electrode mixture layer and improving the energy density of the battery. Also, since the adhesive strength of the separator at the electrode ends is improved, it is possible to prevent lithium from being deposited at the electrodes, particularly at the negative electrode ends, and thus has the advantage of being excellent in safety.
[0106] The present invention will now be described in more detail with reference to examples and experimental examples.
[0107] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0108] <Production Examples 1 to 4. Production of auxiliary coating composition> Boehmite, tannic acid, styrene butadiene rubber (SBR) and polyvinylidene fluoride (PVDF) were prepared, weighed as shown in Table 1 below, and mixed with N-methylpyrrolidone to prepare auxiliary coating compositions. At this time, the solid content of each auxiliary coating composition prepared was adjusted as shown in Table 1.
[0109] [Table 1]
[0110] <Examples 1 to 5 and Comparative Example 1. Production of electrodes for lithium secondary batteries> To manufacture a positive electrode for a lithium secondary battery, an aluminum thin plate (average thickness: 30 μm) was prepared as a positive electrode current collector, and the positive electrode active material LiNi was used as a positive electrode slurry. 0.7 Co 0.1 Mn 0.2 O 2 97.5 parts by weight; 1 part by weight of carbon nanotubes as a conductive material; and 1.5 parts by weight of PVDF as a binder were weighed out and mixed with N-methylpyrrolidone to prepare a binder.
[0111] Separately, in order to manufacture a negative electrode for a lithium secondary battery, a copper thin plate (average thickness: 30 μm) was prepared as a negative electrode current collector, and a negative electrode slurry was prepared by weighing out 60 to 99 parts by weight of artificial graphite as a negative electrode active material, 0.5 to 20 parts by weight of carbon nanotubes and carbon black as conductive materials, and 0.2 to 20 parts by weight of styrene-butadiene rubber (SBR) as a binder, and mixing this with water.
[0112] Each electrode current collector was fixed to a coating device equipped with a slot die, and the electrode slurry and the auxiliary coating composition prepared in the Preparation Example were supplied through the slot die to manufacture an electrode for a lithium secondary battery. The types of electrodes manufactured and the types of auxiliary coating compositions supplied through the slot die are as shown in Table 2 below. The slot die is formed by combining an upper die and a lower die having a chamber, and a shim member is interposed between the upper die and the lower die. The shim member has a structure in which a plate-shaped body has a hollow communicating with the chamber. Specifically, the shim member has a structure, as shown in FIG. 3(b), in which an outlet port is provided on one side through which the electrode slurry supplied through the hollow is discharged, and includes one partition wall that divides the hollow so that the discharged electrode slurry is divided and supplied. In addition, a supply groove is provided on the partition and the inner end of the main body arranged parallel to the partition so that the auxiliary coating composition manufactured in the manufacturing example is discharged to both sides of each discharge port (first discharge port and second discharge port) divided by the partition, and the partition has two supply grooves and the main body has one discharge lip, and a through-hole penetrating in the thickness direction of the shim member is formed about 0.5 to 2 mm inward from the inlet of the supply groove. In addition, as shown in Figure 5, the discharge lip to which the auxiliary coating composition is supplied may have a shape 338 in which the partition and the inner end of the main body arranged parallel to the partition are located inside the upper die and the lower die, and are about 100 μm inward based on the side of the upper die and the lower die.
[0113] [Table 2]
[0114] <Comparative Examples 2 to 5. Production of Electrodes for Lithium Secondary Batteries> The electrode slurry was applied onto an electrode current collector using a slot die with a shim member having no supply groove, and the auxiliary coating composition shown in Table 3 below was applied to the edge of the continuously applied electrode slurry to prepare an electrode for a lithium secondary battery.
[0115] [Table 3]
[0116] <Experimental Example> In order to evaluate the sliding improvement effect at the end of the electrode mixture layer of the electrode for a lithium secondary battery according to the present invention, a scanning electron microscope (SEM) was taken of the cross section of the electrodes manufactured in each of the examples and comparative examples. From the images taken, (1) the difference (|ab|) between the length (a) of the surface in contact with the electrode current collector and the length (b) of the surface not in contact with the electrode current collector of each electrode mixture layer; and (2) the sliding angle (i.e., the "tilt angle") at the end were analyzed, and the results are shown in Figures 6 and 7 and Table 4 below.
[0117] [Table 4]
[0118] As shown in Table 4 and the accompanying FIGS. 6 and 7, it can be seen that the electrode for a lithium secondary battery according to the present invention has an improved sliding phenomenon at the end of the electrode mixture layer.
[0119] Specifically, in the electrodes of the present invention in which an auxiliary coating layer is simultaneously coated on the end of the electrode mixture layer during the formation of the electrode mixture layer, the difference (|ab|) between the length (a) of the surface of the electrode mixture layer that contacts the electrode current collector and the length (b) of the surface that does not contact the electrode current collector, i.e., the difference (|ab|) in the length of the upper surface of the electrode mixture layer, was found to be less than 2 mm, specifically 1.2 mm or less, in the case of the positive electrode, and less than 8 mm, specifically 7.5 mm or less, in the case of the negative electrode. It was also confirmed that the electrodes of the examples had sliding angles exceeding 80° for both the positive electrode and the negative electrode.
[0120] From these results, it can be seen that the electrode for a lithium secondary battery according to the present invention includes an auxiliary coating layer including inorganic particles, a phenol compound, and a binder at an end of an electrode mixture layer including an electrode active material, thereby improving the thickness difference at the end of the electrode mixture layer, thereby improving the energy density of the battery, and improving the adhesive strength of the separator at the end of the electrode, thereby preventing lithium precipitation at the electrode, particularly at the end of the negative electrode.
[0121] Although the present invention has been described above with reference to preferred embodiments thereof, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and variations to the present invention without departing from the spirit and technical scope of the present invention as set forth in the claims below.
[0122] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims. [Explanation of symbols]
[0123] 100: Slot die 110: Upper die 120: Lower die 130, 230, 330: Shim parts 131, 231, 331: Main unit 132:Hollow 133, 233, 333: Bulkhead 134, 334: Discharge port 135, 235, 335: Supply groove 136, 236, 336: Discharge lip 237: Penetration 338: Distance between the outlet and the outlet lip C: Chamber
Claims
1. Electrode current collector, an electrode mixture layer provided on the electrode current collector and containing an electrode active material; and An auxiliary coating layer is provided on the electrode current collector and is located at an end of the electrode mixture layer, The auxiliary coating layer includes inorganic particles, a phenolic compound, and a binder, The electrode for a lithium secondary battery, wherein the difference (|a-b|) between the length (a) of the surface of the electrode mixture layer that is in contact with the electrode current collector and the length (b) of the surface that is not in contact with the electrode current collector is 8 mm or less.
2. 2. The electrode for a lithium secondary battery according to claim 1, wherein the inorganic particles include one or more aluminum minerals selected from the group consisting of boehmite, gibbsite, diaspore, alunite, and nepheline.
3. The phenolic compound includes one or more of tannic acid, baicalin, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, piceatannol, pyrogallol, and ellagic acid. Electrode for lithium secondary battery according to claim 1.
4. 2. The electrode for a lithium secondary battery according to claim 1, wherein the auxiliary coating layer comprises inorganic particles in an amount of 50 wt% or more based on the total weight of the auxiliary coating layer.
5. The electrode for a lithium secondary battery according to claim 1 , wherein the auxiliary coating layer has a structure surrounding an end surface of the electrode mixture layer and forms one layer with the electrode mixture layer.
6. 2. The electrode for a lithium secondary battery according to claim 1, wherein the auxiliary coating layer has a thickness that is 70% to 100% of the average thickness of the electrode mixture layer.
7. 2. The electrode for a lithium secondary battery according to claim 1, wherein the end of the electrode mixture layer has an inclination angle of 50° or more.
8. The electrode slurry including the electrode active material and the auxiliary coating composition are simultaneously coated on the electrode current collector to produce an electrode having an auxiliary coating layer disposed on an end of an electrode mixture layer including the electrode active material, The auxiliary coating composition comprises inorganic particles, a phenolic compound, and a binder; a difference (|a-b|) between a length (a) of a surface of the electrode mixture layer that is in contact with the electrode current collector and a length (b) of a surface of the electrode mixture layer that is not in contact with the electrode current collector is 8 mm or less.
9. The method of claim 8, wherein the inorganic particles are contained in an amount of 50 wt% or more based on the total weight of the auxiliary coating composition.
10. The phenolic compound includes one or more of tannic acid, baicalin, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, piceatannol, pyrogallol, and ellagic acid. The method for producing an electrode for a lithium secondary battery according to claim 8.
11. 9. The method of claim 8, wherein the phenol compound is contained in an amount of 0.1 to 5 wt % based on the total weight of the auxiliary coating composition.
12. The present invention includes a step of simultaneously coating an electrode slurry containing an electrode active material and an auxiliary coating composition on an electrode current collector to produce an electrode having an auxiliary coating layer disposed on an end of an electrode mixture layer containing an electrode active material, the difference (|a-b|) between the length (a) of the surface of the electrode mixture layer that is in contact with the electrode current collector and the length (b) of the surface that is not in contact with the electrode current collector is 8 mm or less; The electrode slurry and the coating of the auxiliary coating composition are simultaneously extruded through a slot die; The slot die includes an upper die having a chamber for accommodating an electrode slurry, a lower die facing the upper die, and a plate-shaped shim member located between the upper die and the lower die, the plate-shaped shim member having a hollow in a body communicating with the chamber and provided with a discharge port for discharging the electrode slurry from the hollow, The shim member includes a supply groove for supplying the auxiliary coating composition to both ends of the discharge port.
13. The shim member includes a partition wall that divides a hollow space so that electrode slurry is discharged into the main body in a divided manner, The method for manufacturing an electrode for a lithium secondary battery according to claim 12, wherein the partition has a supply groove for supplying an auxiliary coating composition to an edge of each electrode slurry that is separately discharged.
14. the supply groove includes a through-portion that penetrates the shim member in a thickness direction, The method for manufacturing an electrode for a lithium secondary battery according to claim 13, wherein the through-hole is formed with a predetermined length inward from a discharge lip through which the auxiliary coating composition is discharged.
15. 15. The method of claim 14, wherein the outlet and the lip of the shim member are in contact with each other on the inner side of one side of the upper die and the lower die on which the outlet and the lip are provided.
Citation Information
Patent Citations
Secondary battery separator comprising dispersant, and manufacturing method therefor
EP3790079A1
Control of coated edges
JP2005509247A
Electrode plate, cell using the same, manufacturing method of electrode plate, manufacturing method of cell using electrode plate, and die head
JP2020072007A
Nonaqueous electrolyte secondary battery
JP2021026885A
Die coating device
JP2021120148A